2015
DOI: 10.3393/ac.2015.31.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Metastatic Goblet-Cell Carcinoid Tumor Treated With Cytoreductive Surgery and Intraperitoneal Chemotherapy

Abstract: We report a case of a goblet-cell carcinoid tumor of the appendix which metastasized to the peritoneum and was treated by using cytoreductive surgery (CRS) with intraperitoneal chemotherapy. A 47-year-old male presented with chronic constipation and was diagnosed as having a rectal adenocarcinoma with a signet-ring-cell component under colonoscopy. Computed tomography suggested peritoneal metastases with diffuse nodular parietal peritoneal thickening of the entire abdomen and focal invasion of the upper rectum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Yan et al[17] in their series of 26 patients reported that nine patients (35%) with metastatic GCC failed to stain for neuroendocrine marker. The explanation for this finding remains elusive[17-21]. …”
Section: Clinical Presentationmentioning
confidence: 99%
“…Yan et al[17] in their series of 26 patients reported that nine patients (35%) with metastatic GCC failed to stain for neuroendocrine marker. The explanation for this finding remains elusive[17-21]. …”
Section: Clinical Presentationmentioning
confidence: 99%
“… 13 Cytoreductive surgery and intraperitoneal chemotherapy have been employed for the peritoneal disease. 17 Extra‐appendiceal GCA usually exhibit aggressive behavior and present in advanced stages. 1 , 10 Prognosis depends on stage and tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…The colorectal neuro-endocrine tumour (NET) including GCCC does not present with any specific symptoms, however maypresent with abdominal pain, large mass, constipation, intestinal obstruction, tenesmus, haematochezia or anal pain, however as other goblet cell carcinomas, GCCCs tumour does not illicit carcinoid syndrome. These tumours can be detected incidentally during routine investigations such as colonoscopy (17,30,31,32).…”
Section: Mcdole Et Al From Washington University Inmentioning
confidence: 99%
“…Synaptophysin (Trans-membrane Channel Protein) is a common specific but not sensitive endocrine marker, it is used in carcinoid tumour, Merkel cell carcinoma (MCC) and small cell carcinoma (3,32,40,44,45).…”
Section: Mcdole Et Al From Washington University Inmentioning
confidence: 99%
See 1 more Smart Citation